Seasonal incidence of insect pests and their natural enemies in mustard ecosystems: A comprehensive review - Prabhu Prasanna Pradhan; Ashok Kumar Sharma; Rudra Narayan Borkakati (Journal of Oilseed Brassica, 2026)
Mustard (Brassica spp.) is a major oilseed crop in India and is prone to attack by a wide range of insect pests throughoutits growth stages, leading to substantial yield losses. Among these, the mustard aphid Lipaphis erysimi (Kalt.), mustardsawfly Athalia lugensproxima, flea beetle Phyllotreta cruciferae, and painted bug (Bagrada cruciferarum and B. hilaris)are of major economic importance. This review synthesizes decades of research on the seasonal incidence, populationdynamics, and influencing meteorological parameters of these pests, along with the occurrence of their natural enemies.Studies consistently reveal that L. erysimi appears from November to April, with peak activity during January-Februaryunder temperature ranges of 17-24°C and relative humidity between 60-85%. Rainfall exerts variable effects, with lightshowers favouring population build-up and heavy rains causing dislodgement. Mustard sawfly incidence generally beginsin October-December, with optimal development at temperatures between 19-30°C, while flea beetle populations peak inFebruary. Painted bugs show seedling-stage damage and activity peaks either in winter or during crop maturity dependingon the species. Natural enemies, particularly Diaeretiella rapae, Coccinella septempunctata, Cheilomenes sexmaculata,syrphid flies, and lacewings, play a vital role in pest suppression, with parasitism levels often exceeding 80-90% during latecrop stages. Temperature, humidity, sunshine hours, wind velocity, and crop phenology significantly influences the timingand intensity of both pest and predator populations. Understanding these seasonal patterns are critical for developingtimely, ecologically sound pest management strategies in mustard cultivation.